SETTLEMENT BEHAVIOUR AND SIZE OF MUSSEL LARVAE FROM THE FAMILY MYTILIDAE (Brachidontes erosus (Lamarck, 1819), Brachidontes rostratus (Dunker, 1857), Trichomya hirsutus (Lamarck, 1819), and Mytilus galloprovincialis Lamarck, 1819 - Medy Ompi (JOURNAL OF COASTAL DEVELOPMENT, 2010)
This study examines the settlement behaviour of the mytilids Mytilus galloprovincialis, Brachidontes erosus, Brachidontes rostratus, and Trichomya hirsutus larvae in response to different substrata: which were byssus threads of these four mussel species, coconut thread, and Polyvinyl chloride (PVC).  The number of settlers on different substrata in the laboratory was analysed separately for each species using One-way ANOVA.  A significant effect of substratum was found for all species tested.  Larvae of T. hirsutus and B. erosus settled preferentially on conspecific byssus threads, while B. rostratus and M. galloprovincialis showed a similar trend.  Settlement data from the field was analysed using two-way ANOVA with species and substrata as the main effect. Settlement was effected by species, but not by substrata.  However, the overall settlement pattern indicated a conspecific preference with the lowest number of settlers on PVC substratum.  Small size of settlement larvae of B erosus comparing to settlement larvae of T hirsutus, M galloprovinciallis, and B rostratus was observed.